INFLUENCE OF ALTITUDINAL ZONES ON THE TRANSFORMATION OF RURAL SETTLEMENT NETWORK OF NORTH OSSETIA - ALANIA IN 1959-2010 - Pavel P. Turun; Irina V. Chernova (Вестник Северо-Кавказского федерального университета, 2022)
Discusses the dynamics of rural population of the Republic of North Ossetia - Alania by periods between population census. Identifies typical features of transformation of the system of rural settlement at different altitude levels.